PARENTAL ANXIETY AND DEFENCE MECHANISM REFLECTED IN JODI PICOULT’S MY SISTER’S KEEPER - Yohanes Tuaderu; Diana Kristianti Sarereake (Sekolah Tinggi Bahasa Asing Prayoga Padang, 2026)
This study examines parental anxiety and defense mechanisms in Jodi Picoult's novel My Sister's Keeper through a literary psychoanalytic approach. The focus of this study is the psychological response of Sara and Brian Fitzgerald – the parents - to the severe leukemia that threatens the life of their daughter, Kate. It also examines how this response affects their relationship with Anna, the savior sister. This study asks three fundamental questions related to: (1) the causes of parental anxiety, (2) the manifestations of defense mechanisms, and (3) the consequences of these mechanisms on the parent-child relationship between the parents and Anna. This study uses a qualitative descriptive method, with close reading as the primary data-collection technique. The analysis is based on Sigmund Freud's theory of anxiety and Anna Freud's theory of defense mechanisms. At the end of the study, the researchers found that the main source of parental anxiety was the constant threat of losing Kate, which caused emotional distress, fear, and helplessness. To cope with this anxiety, Sara and Brian unconsciously used defense mechanisms such as denial, rationalization, repression, and suppression. These psychological responses shaped their decisions, including the controversial choice to conceive Anna as a genetically compatible donor. Furthermore, this study found that this defense mechanism significantly impacted family relationships, particularly by creating emotional tension and undermining Anna's autonomy as a savior sibling. The study concluded that the parents' actions in My Sister's Keeper were not only driven by love and sacrifice but also shaped by unconscious psychological processes.